Can Attacks against Embassies Serve as a Basis for the Invocation of Self-Defence? A Reply to Gábor Kajtár and Gergő Balázs. (25th September 2021) - Ruys, Tom
Abstract: In their article 'Beyond Tehran and Nairobi', Gábor Kajtár and Gergő Balázs examine whether attacks against embassies can qualify as 'armed attacks' and thus serve as a basis for the invocation of self-defence. Based on a survey of relevant state practice and opinio juris, and building on an impressive database encompassing more than 730 incidents, the authors conclude that this question must, in all likelihood, be answered in the negative. This Reply raises the question whether the analysis and the material unearthed ultimately corroborate the conclusion which the authors distil therefrom. Upon closer scrutiny, it is suggested that there may be other, more compelling, inferences to be drawn from the material explored than the one hinted at by Kajtár and Balázs.